Theological themes in Ricardo's papers and correspondence. Issue 4 (4th July 2017) - Cremaschi, Sergio
Abstract: I review evidence from published and unpublished sources on Ricardo's theological ideas. The main focuses of interest are the existence of a natural morality independent of religious confessions, morality as the essence of religion, uselessness of theological speculation, justification of toleration for everybody, including atheists, and the miscarriage of any attempt at a philosophical theodicy. The paper explores also the connection between Ricardo's interest for theodicy and his views on the scope and method of political economy and suggests that his opinion that political economy should be a secular and value-free science close to mathematics depends precisely on theological reasons.